Job Satisfaction as a Predictor of Counterproductive Work Behavior with Work Engagement as a Mediator for Employees in Jakarta - Irene Kezia Susilo; Putu Tommy Yudha Sumatera Suyasa; I Made Budiana (PT Publikasiku Academic Solution, 2024)
The aim of the researchers in conducting research was to see the relationship between Job Satisfaction and Counterproductive Work Behavior with Work Engagement as a mediator during the Covid-19 Pandemic situation. The hypothesis in this research is. Researchers used a quantitative approach method, data was collected through questionnaires distributed online at a certain time. Data processing and analysis techniques were carried out using the Statistical Product and Service Solution (SPSS) program version 25 for Windows and the LISREL program version 8.8 for Windows. The results of this research show that there is a positive and significant mediating role, which means that Work Engagement has a negative and significant mediating role on Counterproductive Work Behavior. This shows that Job Satisfaction will form high Work Engagement so that it will help reduce Counterproductive Work Behavior in employees